2021
DOI: 10.1093/molbev/msab080
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Gene Transfer and Gene Duplication of β-Fructofuranosidase Confer Lepidopteran Insects Metabolic Benefits

Abstract: Horizontal gene transfer (HGT) is a potentially critical source of material for ecological adaptation and the evolution of novel genetic traits. However, reports on post-transfer duplication in organism genomes are lacking, and the evolutionary advantages conferred on the recipient are generally poorly understood. Sucrase plays an important role in insect physiological growth and development. Here, we performed a comprehensive analysis of the evolution of insect β-fructofuranosidase transferred from bacteria v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 75 publications
(95 reference statements)
0
13
0
Order By: Relevance
“…The expression of BmSUC1 in the luminal of the silk gland is higher than that in the glandular ( Figure 2 D,F), and Guo et al also detected the presence of BmSUC1 protein in cocoon silk [ 23 ], indicating that silkworm BmSUC1 is synthesized in the glandular and secreted into the luminal to directly interact with silk protein to play its function. The findings of Dai et al suggest that BmSUC1 has a role in maintaining silk gland metabolic homeostasis [ 34 ]. Loss of BmSUC1 resulted in a disturbance of the silk secretion environment, resulting in a decrease in the secretion of sericin protein and a decrease in the content of sericin in the cocoons ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of BmSUC1 in the luminal of the silk gland is higher than that in the glandular ( Figure 2 D,F), and Guo et al also detected the presence of BmSUC1 protein in cocoon silk [ 23 ], indicating that silkworm BmSUC1 is synthesized in the glandular and secreted into the luminal to directly interact with silk protein to play its function. The findings of Dai et al suggest that BmSUC1 has a role in maintaining silk gland metabolic homeostasis [ 34 ]. Loss of BmSUC1 resulted in a disturbance of the silk secretion environment, resulting in a decrease in the secretion of sericin protein and a decrease in the content of sericin in the cocoons ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gene duplication is one of the primary driving forces of genome evolution and a significant mechanism for the establishment of new gene functions (Moore & Purugganan, 2003). Duplicate genes tend to diverge in regulatory and coding regions to produce novel regulatory profiles, novel peptides, or specialized subfunctions (Rogers et al ., 2014; Man & Gallagher, 2020; Dai et al ., 2021). In this study, we observed sequence and exon/intron size differences across 8 lipocalin groups.…”
Section: Discussionmentioning
confidence: 99%
“…Among Lepidoptera, evidences of host-parasite interactions in moths reveal that sequences transmitted by endosymbiotic microorganisms can affect the host fitness, metabolism, reproduction, population dynamics, and genetic diversity [11]. Concerning feeding and host adaptation, digestive and metabolic benefits conferred by HGT to functional enhancement in favor of lepidopteran insects, such as b-fructofuranosidase [12] and cysteine synthase genes [13].…”
Section: -Albert Einsteinmentioning
confidence: 99%